The following theorem is from Rudin's $\textit{Principles of Mathematical Analysis}$.

$\textbf{Theorem:}$ Let $\alpha$ be monotonically increasing on $[a,b]$. Suppose $f_n \in \mathscr{R} (\alpha)$ on $[a,b]$, for $n = 1,2,3,...,$ and suppose $f_n \rightarrow f$ uniformly on $[a,b]$. Then $f \in \mathscr{R}(\alpha)$ on $[a,b]$, and $$\int_{a}^{b} f d\alpha = \lim_{n \rightarrow \infty} \int_{a}^{b} f_n d \alpha. \tag{*}$$

$\textbf{Proof}:$ Put $$\epsilon_n = \sup_{a \leq x \leq b}|f_n (x) - f(x)|.$$ Then $$f_n - \epsilon_n \leq f \leq f_n + \epsilon_n,$$ so that the upper and lower integrals of $f$ satisfy \begin{equation}\int_a^b (f_n - \epsilon_n) d\alpha \leq \int_{\_} f d \alpha \leq \int^{\_} f d \alpha \leq \int_a^b (f_n + \epsilon_n) d \alpha. \tag{1}\end{equation}


$$0 \leq \int^{\_} f d\alpha - \int_{\_} f d \alpha \leq 2 \epsilon_n [\alpha (b) - \alpha (a) ] \tag{2}.$$ Since $\epsilon_n \rightarrow 0$ as $n \rightarrow \infty$, the upper and lower integrals of $f$ are equal.

Thus $f \in \mathscr{R}(\alpha)$. Another application of $(1)$ now yields $$\left| \int_a^b f d \alpha - \int_a^b f_n d \alpha \right| \leq \epsilon_n [\alpha(b) - \alpha(a)], \tag{3}$$ which implies the result $(*)$.

$\textbf{My question:}$ Where do lines $(2)$ and $(3)$ come from? I think line $(2)$ just comes from rearranging line $(1)$ via basic operations, but I don't see where the integrals went.


(1) consists of 3 inequalities:

$$\begin{equation}\int_a^b (f_n - \epsilon_n) d\alpha \leq \int_{\_} f d \alpha \tag{1.1}\end{equation}$$

$$\begin{equation}\int_{\_} f d \alpha \leq \int^{\_} f d \alpha \tag{1.2}\end{equation}$$

$$\begin{equation}\int^{\_} f d \alpha \leq \int_a^b (f_n + \epsilon_n) d \alpha. \tag{1.3}\end{equation}$$

(1.2) gives you

$$0 \leq \int^{\_} f d\alpha - \int_{\_} f d \alpha$$

with (1.1) and (1.3) you get:

$$\begin{align*}\int^{\_} f d\alpha - \int_{\_} f d \alpha &\le \int_a^b (f_n + \epsilon_n) d \alpha - \int_a^b (f_n - \epsilon_n) d\alpha \\ &= 2\varepsilon_n\int_a^b 1\, d\alpha \\ &= 2\varepsilon_n[\alpha(b) - \alpha(a)]\end{align*}$$

(3) you get by similar steps…

  • $\begingroup$ This is simple to follow. Thanks. $\endgroup$ – amarney Mar 21 '17 at 13:53

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.